1988
DOI: 10.3109/10715768809068553
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lipid Peroxidation in Hyperthyroid Patients: Suppression by Propylthiouracil Treatment

Abstract: Plasma and urinary levels of thiobarbituric acid reactive substances (TBAR) were determined in 24 hyperthyroid patients, 19 hypothyroid subjects, 35 controls, and 17 hyperthyroid patients before and after propylthiouracil (PTU) treatment (400 mg/day for 2-3 months), as indexes of lipid peroxidation. These measurements were carried out together with t-butyl hydroperoxide (t-BHP)-induced oxygen uptake and visible chemiluminescence in erythrocytes as functional tests related to the antioxigenic capacity of cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
3
35
0
2
Order By: Relevance
“…Accordingly, PTU has been shown to act as a highly efficient scavenger of OH radicals, to be a potent inhibitor of lipid peroxidation in model membranes (Hicks et al 1992) and to inhibit H 2 O 2 production in neutrophils (Imamura et al 1986) or Graves' retro-ocular fibroblasts (Heufelder et al 1992). It has also been observed that hyperthyroid patients treated with PTU have decreased serum MDA levels, suggesting that PTU may scavenge ROMs or may directly protect lipids from peroxidative attack (Videla et al 1988). In accordance with these results, in the present study tissue MDA was increased in the lung, liver, kidney and ileum of whole-body irradiated rats, indicating the presence of radiation-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, PTU has been shown to act as a highly efficient scavenger of OH radicals, to be a potent inhibitor of lipid peroxidation in model membranes (Hicks et al 1992) and to inhibit H 2 O 2 production in neutrophils (Imamura et al 1986) or Graves' retro-ocular fibroblasts (Heufelder et al 1992). It has also been observed that hyperthyroid patients treated with PTU have decreased serum MDA levels, suggesting that PTU may scavenge ROMs or may directly protect lipids from peroxidative attack (Videla et al 1988). In accordance with these results, in the present study tissue MDA was increased in the lung, liver, kidney and ileum of whole-body irradiated rats, indicating the presence of radiation-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In man, hyperthyroidism is characterized by significant changes in circulating parameters related to oxidative stress, including (i) higher levels of lipid peroxidation indicators (40)(41)(42)(43)(44)(45)(46)(47)(48)(49); (ii) enhancement in hydrogen peroxide and lipid hydroperoxide levels (49); and (iii) diminished levels of antioxidants such as a-tocopherol (41), coenzyme Q (44), ascorbic acid (41), and reduced thiols (42,46,50). These changes correlated with the enhancement in urinary lipid peroxidation products (40) and chemiluminescence response (51) and are either significantly reduced or normalized by thyrostatic therapy or antioxidant supplementation (40-46, 49, 50).…”
Section: T 3 -Induced Enhancement Of Liver O 2 Consumption and Oxidatmentioning
confidence: 99%
“…There is supporting evidence that lipid peroxidation may play a role in the potential anticarcinogenic effect of other breast cancer factors, including soy (28,(181)(182)(183)(184)(185)(186)(187), marine n-3 fatty acids (46), thyroid diseases (188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202), green tea (203)(204)(205)(206)(207), vitamin D (208), calcium (209)(210)(211)(212), folate (213), and isothiocyanates (214)(215)(216)(217).…”
Section: Other Suspected Protective/risk Factors For Breast Cancermentioning
confidence: 99%